The effect of my occupational engagement program (MYOCEP) on cognitive functions, social relationship, and quality of life among older people with mild dementia in institution / Syamsul Anwar Sultan Ibrahim - Sultan Ibrahim, Syamsul Anwar (2022)
The proportion of older people in Malaysia is increasing and it is anticipated that Malaysia will become an ageing country by the year 2030. Increased in age often associated with increase in disability or risk of diseases. In addition to the changes in health status, there are also changes in socio-demographic and socio-fabric characteristics of Malaysian society that could lead to the influx of older population in older people institutions. On top of that, several studies also indicated that the health status amongst older people in institutions are deteriorating. There is a decline in functional abilities and health statuses such as musculoskeletal related conditions, and cognitive related disease such as dementia. Older people with dementia will experience the cognitive difficulties that are believed to have a significant impact their daily life. There are several approaches which can be classified as either pharmacological or non-pharmacological interventions for people with dementia. Currently, the non-pharmacological interventions for dementia are increasingly considered as the alternative treatment in providing a positive benefits in delaying the disease’s progression and improving the quality of life. However, the information regarding the intervention toward dementia in institution is inconclusive and lack of integration between approaches as medium of intervention. Therefore, this study intended to identify the effect of a newly developed intervention known as MyOCEP to improve cognitive functions, social relationship, and quality of life among older people in institution. There are two phases in this study. Phase one described the development process of the intervention in four different stages. In phase two, randomized controlled trial study has been conducted two identify the effectiveness of the intervention. Thirty two older people with mild dementia who fit into the inclusion criteria were randomly allocated to the intervention and control groups. Participants in the intervention group received fourteen sessions of intervention program conducted by trained occupational therapists while participants in the control group only received standard occupational therapy intervention. Lowenstein Occupational Therapy Cognitive Assessment – Geriatric (LOTCA-G), Location Learning Test (LLT), Friendship Scale (FS), and WHOQOL-BREF were used to measure the cognitive functions, social relationship, and quality of life. Independent occupational therapists administered all outcome measures before and immediately after the program. At the end of seven weeks, participants in the experimental group improved significantly in cognitive functions in the subtest of orientation for time (orientation domain), object constancy (perception domain), block design and drawing a clock (visuomotor organization domain), categorization (thinking operations domain), everyday objects (memory domain), and attention and concentration domain, social relationship, and the domains of quality of life (physical, psychological, social, and environment) in comparison to the participants in the control group on a between group analysis. These results provide evidence to support the use of multi approaches intervention in improving cognitive functions, social relationship and quality of life for older people with mild dementia in institution. Findings from this study suggest that engagement in occupational activities is beneficial in the milder stages of dementia, potentially in delaying the progress of the disease as well as minimizing the risk of further deterioration thus improving the quality of life. This research is confined to an elderly institution and also limited to the category of older people with mild dementia. Therefore, a wide scale of randomized testing together with the evaluation on functional aspect in daily living might be necessary in the future.